2015
DOI: 10.5455/2349-2902.isj20150205
|View full text |Cite
|
Sign up to set email alerts
|

Studying major amputations in a developing country using Amit Jain's typing and scoring system for diabetic foot complications - time for standardization of diabetic foot practice

Abstract: It is estimated that around 347 million people in the world are diagnosed with diabetes mellitus. 1 Indian is one of the country with very high prevalence of diabetes in the world which is predicted to increase to 120.9 million by 2030. 2 It is estimated that approximately 23.6 million people in United States have diabetes mellitus. 3 It is predicted that 1 in 3 American adults will have diabetes by 2050. 4 Diabetes affect 3% of the UK population. 5 Diabetic foot is one of the most common and distressing compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
1
25
0
6
Order By: Relevance
“…Our study showed that major amputations were common in similar to Jain et al series. [9] Below knee amputation was the commonest amputation in our series and also in Jain et al series. [9] The commonest cause for major amputation in this study was wet gangrene.…”
Section: Discussionsupporting
confidence: 67%
“…Our study showed that major amputations were common in similar to Jain et al series. [9] Below knee amputation was the commonest amputation in our series and also in Jain et al series. [9] The commonest cause for major amputation in this study was wet gangrene.…”
Section: Discussionsupporting
confidence: 67%
“…Around 15% of diabetic patients will develop foot ulcers in their life time and this is known to cause amputation in 85% of the cases, in India approximately 45,000 lower limbs are amputated every year due to diabetic foot complications [14] .…”
Section: Discussionmentioning
confidence: 99%
“…8,13,20 The surgical scoring has 16 factors and it includes clinical, anatomical, radiological and surgical finding that is unique of this scoring system. 20 Various studies have shown that more than 80% of major amputation done in diabetic foot had a score or more than 16.…”
Section: 18mentioning
confidence: 99%
“…[16][17][18] Studies also concluded that type 1 diabetic foot complication are the most common cause of major amputations in developing country like India, with 76.9% of patients who underwent major amputation had type 1 diabetic foot complication. 8,16 Jain et al also showed for the first time that type 1 diabetic foot complication are the most common cause of mortality (78.38%). 19 Nather et al failed to review and refer these studies in his article suggesting how to choose a classification with advantages and disadvantages of various classifications on diabetic foot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation